Neonatal presentation of COG6‐CDG with prominent skin phenotype. Issue 1 (7th August 2020) - Komlosi, Katalin; Gläser, Selina; Kopp, Julia; Hotz, Alrun; Alter, Svenja; Zimmer, Andreas D.; Beger, Carmela; Heinzel, Stefan; Schmidt, Christoph; Fischer, Judith
Abstract: Many of the genetic childhood disorders leading to death in the perinatal period follow autosomal recessive inheritance and bear specific challenges for genetic counseling and prenatal diagnostics. Often, affected children die before a genetic diagnosis can be established, thereby precluding targeted carrier testing in parents and prenatal or preimplantation genetic diagnosis in further pregnancies. The clinical phenotype of congenital disorders of glycosylation (CDG) is very heterogeneous and ranges from relatively mild symptoms to severe multisystem dysfunction and even a fatal course. A very rare subtype, COG6‐CDG, is caused by deficiency of subunit 6 of the conserved oligomeric Golgi complex and is usually characterized by growth retardation, developmental delay, microcephaly, liver and gastrointestinal disease, joint contractures and episodic fever. It has been proposed that a distinctive feature of COG6‐CDG can be ectodermal signs such as hypohidrosis/hyperthermia, hyperkeratosis and tooth anomalies. In a Greek family, who had lost two children in the neonatal period, with prominent skin features initially resembling restrictive dermopathy, severe arthrogryposis, respiratory insufficiency and a rapid fatal course trio whole‐exome sequencing revealed the homozygous nonsense mutation c.511C>T, p.(Arg171*) in the COG6 gene. Skin manifestations such as dry skin and hyperkeratosis have been reported in only five out of the 21 reported COG6‐CDG cases so far, including two patients with the c.511C>T variant in COG6 but with milder ectodermal symptoms. Our case adds to the phenotypic spectrum of COG6‐CDG with prominent ectodermal manifestations at birth and underlines the importance of considering CDG among the possible causes for congenital syndromic genodermatoses.